The contribution of Dutch doctors in Global Health and Tropical Medicine to research in global health in low- and middle-income countries: an exploration of the evidence. (January 2020) - Mooij, Rob; Jurgens, Esther MJ; van Dillen, Jeroen; Stekelenburg, Jelle
Results from medical research from high-income countries may not apply to low- and middle-income countries. Some expatriate physicians combine clinical duties with research. We present global health research conducted by Dutch medical doctors in Global Health and Tropical Medicine in low- and middle-income countries and explore the value of their research. We included all research conducted in the last 30 years by medical doctors in Global Health and Tropical Medicine in a low- and middle-income country, resulting in a PhD thesis. Articles and co-authors were found through Medline. More than half of the 18 identified PhD theses concerned maternal health and obstetrics, and the majority of the research was conducted in low-income countries, mostly in rural hospitals. Over 70 local co-authors were involved. Different aspects of these studies are discussed.